Empowering Women Through Hydroponic Farming: A Case Study of Community Service Program in Purwosari Village - Adelia, Sabrina Puspa; Yunesa, Anggun Maryam; Haryanto, Bayu Dwi; Syahputro, Ivan Bagus Dwi; Fitria, Reva; Kirom, Zaki Naufal; Rizki, Isni Infadiil; Soraya, Fina Aidah; Amin, Muhamad Sodikul; Asih, Nawang Wulan Retno; et al. (Proceedings Series on Social Sciences & Humanities, 2025)
This study explores a hydroponic farming initiative implemented through Muhammadiyah University of Purwokerto’s Community Service Program (KKN) in Purwosari Village, Indonesia. Targeting Women Farmers Groups (KWT), the project tackles limited arable land and poor soil by introducing a sustainable hydroponic system using PVC pipes and plastic bottles. Employing a community based participatory research (CBPR) approach, the program provides hands-on training in deep water culture (DWC) systems and high-value crop cultivation (e.g., mustard greens, celery). Qualitative methods, including interviews and participant observation, assessed outcomes. Results show success in three areas that is technical empowerment (92% mastered system maintenance), economic benefits, and strengthened community collaboration. The project supports SDGs 2 (Zero Hunger) and 12 (Responsible Consumption), reducing water use by 85% versus traditional farming. Challenges included initial resistance and nutrient management, mitigated through adaptive training. The initiative highlights how student community partnerships can transfer agricultural technology while empowering women in rural development. Recommendations include creating local mentor networks and integrating hydroponics into village economic programs for sustainability. This model offers replicable strategies for resource limited communities.